Implementasi Kurikulum Merdeka Belajar dalam Meningkatkan Motivasi Belajar Siswa Kelas X di SMA Muhammadiyah 1 Sukoharjo - Muhammad Fajrul Shodiq; Edy Muslimin; Muhammad Yunan Hidayat (At Turots: Jurnal Pendidikan Islam, 2025)
This study explores the implementation of the Independent Learning Curriculum (Kurikulum Merdeka Belajar) and its impact on enhancing learning motivation among Grade X students at SMA Muhammadiyah 1 Sukoharjo during the 2023/2024 academic year. Employing a descriptive qualitative method, the research involved field observations, interviews with school leaders, teachers, and students, and document analysis. The findings reveal that the curriculum was implemented through three structured phases: planning, implementation, and evaluation. In the planning phase, the school prioritized teacher training, teaching module preparation, and infrastructural readiness. The implementation phase was marked by differentiated instruction, project-based learning, and diagnostic assessments tailored to student needs. The evaluation phase emphasized reflection and continuous improvement. As a result, students demonstrated increased motivation, characterized by higher engagement, improved classroom atmosphere, and enhanced self-confidence. The study found a decline in the number of students categorized as "less motivated" and a rise in the "moderately motivated" and "highly motivated" categories. These outcomes align with the principles of Self-Determination Theory, emphasizing autonomy, competence, and relatedness. The research concludes that effective implementation of the Independent Learning Curriculum fosters intrinsic motivation and promotes student-centered learning. This study contributes valuable insights for educators and policymakers seeking to strengthen motivation and engagement through adaptive curriculum reforms.